Evaluating success of autotransplantation of embedded/impacted third molars harvested using piezosurgery: a pilot study. (November 2014) - Nagori, Shakil Ahmed; Jose, Anson; Bhutia, Ongkila; Roychoudhury, Ajoy
Abstract Objective. To evaluate the success of autogenous transplantation of embedded/impacted third molars harvested using piezosurgery. Materials and methods. This prospective pilot study enrolled 20 healthy patients with non-restorable first/second molars and a caries-free retrievable embedded/impacted third molar. Piezosurgery was used for removing inter-radicular bone at the recipient socket as well as for bone removal around the donor teeth. Results. After an average follow-up of 16.4 months (SD = 1.9), 18 cases were successful with formation of periodontal ligament around the teeth. One tooth was lost due to infection at 1 month. One patient was lost to follow-up. There was no root resorption or ankylosis in any of the cases. In six donor teeth with complete root formation, root canal treatment was carried out. All the remaining teeth responded positively with vitality testing. Conclusion. Piezosurgery is an effective device if embedded/impacted third molars are to be harvested for successful autogenous transplantation.